Assessing the Intellectual Structure of the Evolving Knowledge Base on ChatGPT in the Field of Education and Health - Murat Demirkol and Nedim Malkoc (Educational Process: International Journal)
Background/purpose –The unprecedented developments in AI-based technologies and large language models such as ChatGPT have exhibited a brand-new territory to be explored. Since its first release in November 2022, the potential utility of ChatGPT has garnered incremental attention in the scientific world, and has already accumulated a great number of studies from diverse fields. The current study was conducted with the purpose of exploring the scientific landscape of the evolving knowledge base related to the use of ChatGPT in the field of education and health through science mapping analysis of published research.